2019
DOI: 10.12740/pp/onlinefirst/92219
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of psychiatric services provided to adults in 2010–2014 based on the National Health Fund data

Abstract: Cel pracyBadanie wskaźników pozwalających na poprawę zdrowia populacji poprzez m.in. poprawę jakości udzielanych świadczeń oraz większą do nich dostępność jest jednym z priorytetów Światowej Organizacji Zdrowia (WHO). W Polsce ma to szczególnie istotne znaczenie w okresie reformy opieki psychiatrycznej, zgodnej z wytycznymi Narodowego Programu Ochrony Zdrowia Psychicznego. Celem prezentowanego opracowania jest analiza świadczeń psychiatrycznych udzielonych osobom dorosłym i sprawozdanych do Narodowego Fundusz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Although the total number of hospital admissions, as well as hospital admissions per 100 thousand population, was significantly reduced after the introduction of Mental Health Centers compared to the 19 months prior to the implementation of the reform, it is still higher than in the period from 2010 to 2014, when it was in the range of 279-307 thousand total hospital admissions and 886-983 hospital admissions per 100 thousand adults [17].…”
Section: Discussion Of Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Although the total number of hospital admissions, as well as hospital admissions per 100 thousand population, was significantly reduced after the introduction of Mental Health Centers compared to the 19 months prior to the implementation of the reform, it is still higher than in the period from 2010 to 2014, when it was in the range of 279-307 thousand total hospital admissions and 886-983 hospital admissions per 100 thousand adults [17].…”
Section: Discussion Of Resultsmentioning
confidence: 82%
“…Between 2010 and 2014, there was a gradual increase in the number of patients treated in all forms of psychiatric care (from 1,319 thousand to 1,480 thousand) and this number was higher than in the period before the reform and lower than after the introduction of Mental Health Centers [17]. With a simultaneous increase in the number of first-time patients in the period following the establishment of Mental Health Centers, the results of the study may suggest that during the 19 months of the operation of Mental Health Centers, the availability of all mental healthcare services was higher both compared to the preceding 19-month period and in comparison to the availability of services between 2010 and 2014.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…According to the WHO, by 2030, depression will be the greatest contributor to the global burden of disease [2]. While there are no systematic epidemiological studies of mental disorders in the general population in Poland [3], a representative survey conducted in 2012 found that about 23% of the Polish population aged 18-64 suffered from mental disorders [4]. Of these, the most common were alcohol abuse (11.90%), specific phobias (4.3%) and depression (3.0%).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a new study conducted during the pandemic period reports increasing rates of anxiety disorders among 18-25-year-olds, 49.1%, and depressive disorders, 52.3%, as well as symptoms occurring as a result of experienced stress, 46% (Vahia et al, 2020). Systematic Polish and foreign reviews depicting the magnitude of mental disorders in young adults are increasingly worrying (Anczewska et al, 2019;Holmes et al, 2020;Pyżalski and Poleszak, 2022).…”
Section: Introductionmentioning
confidence: 99%